2011
DOI: 10.3390/ma4040621
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Crystallinity and Orientation by Hot-Stretching to Improve the Mechanical Properties of Electrospun Partially Aligned Polyacrylonitrile (PAN) Nanocomposites

Abstract: Partially aligned polyacrylonitrile (PAN)-based nanofibers were electrospun from PAN and PAN/single-walled carbon nanotubes (SWNTs) in a solution of dimethylformamide (DMF) to make the nanofiber composites. The as-spun nanofibers were then hot-stretched in the oven to enhance its orientation and crystallinity. With the introduction of SWNTs and by the hot-stretched process, the mechanical properties will be enhanced correspondingly. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 28 publications
6
48
0
Order By: Relevance
“…The average crystallite size can be evaluated using Scherer's relation according to Equation , where “ λ ” is the X‐ray wavelength, “ β ” is the full width at half the maximum of the diffraction peak, “ θ ” is the diffraction angle and “ K ” is the Scherer's constant of the order of unity for an average crystal . Moreover, λ = 1.54 Å and K = 0.90, and β = FWHM at a reflection intensity of 100% . The degree of orientation Π (%) can be estimated by using the fully corrected azimuthal intensity distribution diffracted from the 100 reflection at d‐spacing [Å].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average crystallite size can be evaluated using Scherer's relation according to Equation , where “ λ ” is the X‐ray wavelength, “ β ” is the full width at half the maximum of the diffraction peak, “ θ ” is the diffraction angle and “ K ” is the Scherer's constant of the order of unity for an average crystal . Moreover, λ = 1.54 Å and K = 0.90, and β = FWHM at a reflection intensity of 100% . The degree of orientation Π (%) can be estimated by using the fully corrected azimuthal intensity distribution diffracted from the 100 reflection at d‐spacing [Å].…”
Section: Resultsmentioning
confidence: 99%
“…Crystallinity is generally measured as a ratio of the diffraction portion from the crystalline part of the tubular structure sample, Ic , and the total diffraction from the same sample, I(c + b) . The values of Ic can be obtained after a suitable subtraction of the scattering portion from the background, Ib . %=()italicIcitalicI0.25em100% where I total = I (c + b) . In the X'Pert Pro system, the calculation of crystallinity (%) was done by the user‐defined crystalline (peak region) and amorphous regions (background region) on a frame obtained from the analyzed material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing stretch ratio, more nanotubes were aligned and re-dispersed since the polymer start to orient during the hot-stretching process. Besides, former reports showed that the crystalline polymer tends to recrystallize during the hot-stretching process 31 .…”
Section: Thermal Properties Of the Hot-stretching Mwcnt/pen Compositementioning
confidence: 99%
“…21 With the development of nanotechnology, nanomaterials have become excellent substitutes for peroxidase. 28 Compared with these methods, electrospinning has proved to be a simple, low-cost and versatile way to mass fabricate uniform and continuous nanobers. 23,24 Many methods have been applied to synthesize nanobers, such as self-assembly, 25 template synthesis, 26 stretch method 27 and phase separation.…”
Section: Introductionmentioning
confidence: 99%